Using Thermodynamic Degradation Approach to Quantify Human Stress Response. (11th September 2017) - Boregowda, Satish; Handy, Rod; Sleeth, Darrah; Riches, Naomi
Abstract : The present study provides a thermodynamic degradation approach to model human stress response. Finger skin temperature was used as an indicator of stress response to a stressor (or stressful event) followed by a recovery. The entropy change (Δ S ) is calculated using heat transfer (δ Q ) from the peripheral skin and finger skin temperature (T f ). It was hypothesized that the human stress response, as evidenced by finger skin temperature change, is a quasi-static process. The entropy approach is demonstrated using data from a medical school experimental study. The finger skin temperature was measured under three conditions (relaxation, stressor task, and recovery) during the physiological test profile. The entropy change (Δ S ) is postulated as entropy damage (Δ S D ), which is a metric for measuring the aging or system degradation. The aging-ratio, A aging-ratio, that is, the ratio of entropy change due to stressor to that of recovery, is presented for both male and female subjects. The statisticalt -tests demonstrate statistical significance in human stress response to stressor and recovery states within and between male and female subjects. This novel approach could be valuable to medical researchers, particularly in the field of occupational health to evaluate human exposure to stressful environments.